2014 IEEE/ASME International Conference on Advanced Intelligent Mechatronics 2014
DOI: 10.1109/aim.2014.6878072
|View full text |Cite
|
Sign up to set email alerts
|

Decentralized complex envelope controller for ASAC by virtual mechanical impedances

Abstract: The problem of Active Structural Acoustic Control (ASAC) is to attenuate the radiated sound power by energy injection using structural actuators to modify deflection shapes. Collocated and dual actuator-sensor pairs allow the feedback problem to be formulated as the implementation of virtual mechanical impedances. The approach is based on a two-step process: (1) the virtual impedance is derived from measurements of the primary sound and transfer functions; (2) the centralized or decentralized complex envelope … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Given the number of electrodynamic exciters as , the vector of control inputs for secondary sources is expressed as ⋯ . In this case, the total sound field in the acoustic domain is the sum of the influence of the control input and the disturbance by the noise source and is expressed as follows [14]:…”
Section: A Optimal Vmi For Minimizing the Radiated Sound Power Of A Panelmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the number of electrodynamic exciters as , the vector of control inputs for secondary sources is expressed as ⋯ . In this case, the total sound field in the acoustic domain is the sum of the influence of the control input and the disturbance by the noise source and is expressed as follows [14]:…”
Section: A Optimal Vmi For Minimizing the Radiated Sound Power Of A Panelmentioning
confidence: 99%
“…This is because j is used instead of an integrator to minimize the steady-state error at multiple frequencies, as described in Section II. Next, downsampling is performed using the downsampling factor M after demodulation [14]. This method aims to increase the cycle time of the controller required for noise control over 1 kHz, where passive methods are mainly applied.…”
Section: A Siso System With a Single Sensoriactuatormentioning
confidence: 99%
“…The SSA-measured current and voltage are demodulated (Boulandet et al, 2016) to obtain V c ( f 0 ) and I t ( f 0 ) , the phasors (complex envelope) containing the instantaneous amplitude and phase at the carrier frequency f 0 . The total current I t ( f 0 ) is then corrected according to equation (21) to obtain the vibration global current I glob ( f 0 ) which is used as the error signal in an integral controller (Boulandet et al, 2016; Michau et al, 2014, 2015) in which μ is the convergence coefficient and C ~ ( f 0 ) the identified complex gain of the transfer function of input …”
Section: Ssa Implementationmentioning
confidence: 99%
“…Attempts to reduce sound transmission in large-scale structures such as fuselages have been restricted to only their constituent sub-structures. In Boulandet et al (2014) and Michau et al (2014) sections of fuselages or trim panels are installed in acoustic transmission loss test facilities and equipped with active systems. Nevertheless, a high-performance AVC/ASAC system for a large-scale structure is only realizable by incorporating all sub-structures.…”
Section: Introductionmentioning
confidence: 99%